PTH-045 Effects of an osmotic laxative on the distribution of water between the small and large intestine in humans. (23rd September 2015) - Placidi, E; Hoad, C L; Marciani, L; Gowland, P A; Spiller, R C
Abstract : Introduction: Understanding of the water distribution within the ascending colon (AC) is limited though this is important to study mechanisms of both functional and organic colonic diseases. We have developed novel MRI techniques which allow us to monitor undisturbed colonic function in health and diseases. Methods: To use these new techniques to study the colonic response to two contrasting test meals: a readily absorbable glucose drink and a non-absorbable mannitol drink that stimulates small intestinal secretion and can be used as a model of acute diarrhoeal disease. Eight fasted healthy volunteers (HVs) underwent serial MRI on two occasions to visualise the free water content of the bowel using a previously described method.1 After a baseline scan, they were given a 350 ml 5% mannitol or 5% glucose drink, randomised. HVs were scanned at hourly intervals for 5 h after the drink and were also fed a large 1000 kcal solid/liquid test meal at 3 h to elicit the colonic response to feeding. Results: (mean±SEM) Following the glucose drink the volume of free mobile water in the whole bowel ml did not vary significantly from the fasting baseline being 124±24 vs 112±27 ml at 90 min, p<0.9. Conversely, after the mannitol drink, the water in the whole bowel rose from baseline 109±36 ml to 590±73 ml at 90 min, p<0.008. The difference in the amount of free water that reached the AC at 90 min was particularly marked being 2±1 ml after the glucose drink and 73±20 ml after the mannitol drink, p<0.008. The water that arrived in the AC readily mixed with the colonic contents and caused distension of the AC. Its total (geometric) volume at 90 min rose from 146±17 ml for glucose to 230±18 ml for mannitol, p<0.0004. At later times a bright, homogeneous signal was observed inside the AC, while the for the glucose drink this was heterogeneous and low signal. The second larger meal was followed by a significant fall in total bowel water content from 396±58 ml at time 150 min to 198±37 ml at time 210 min with the mannitol drink (p<0.0011), while no corresponding change was observed for the glucose drink (p<0.7). Conclusion: These images clearly show that the unabsorbable, osmotically active mannitol solution causes secretion in the small bowel. The change in total AC volume with mannitol can largely be explained by the arrival of free mobile water from the small bowel. These methods will be useful in future studies to evaluate mechanisms of diarrhoea and drug intervention and in clinical studies of diarrhoeal disease.